ХАЛҚАРО ИҚТИСОДИЙ МУНОСАБАТЛАР ВА УНДА РЕГИОНЛАРНИНГ РОЛИ - Умарова, А.; Умаров, Е.К. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of globalization of world economy and increasing competition among the major world powers. To overcome the crisis in the context of globalization it is necessary to follow the state ments worked out by the UN for international cooperation in the contest of the development of trade and economic relations in the geo-economic space. To accelerate economic growth, there are given examples of countries of Southeast Asia, and Uzbekistan for the independent years. In conclusion there is emphasized the relevance of the implementation of innovative technologies into the economy, as an important catalyst for strengthening integration processes in international relations.
Keywords: competition; globalization; concentration; integration; liberalization; intellectual resource; innovation; geo-economic space; market; currency; license; GDP; transnational corporation; situation; speculation; expansion; "shadow economy"; region; ecotourism